The Incidence of Lower-Extremity Amputation and Bone Resection in Diabetic Foot Ulcer Patients Treated with a Human Fibroblast-Derived Dermal Substitute. (January 2015) - Frykberg, Robert G.; Marston, William A.; Cardinal, Matthew
ABSTRACT OBJECTIVE: Diabetic foot ulcers (DFUs) are frequently recalcitrant and at risk for infection, which may lead to lower-extremity amputation or bone resection. Reporting the incidence of amputations/bone resections may shed light on the relationship of ulcer healing to serious complications. This study aimed to evaluate the incidence of amputations/bone resections in a randomized controlled trial comparing human fibroblast-derived dermal substitute plus conventional care with conventional care alone for the treatment of DFUs. DESIGN: Ulcer-related amputation/bone resection data were extracted from data on all adverse events reported for the intent-to-treat population (N = 314), and amputations were categorized by type: below the knee, Syme, Chopart, transmetatarsal, ray, toe, or partial toe. Data were analyzed retrospectively for the incidence of amputation/bone resection by treatment. SETTING: Randomized controlled trial. PATIENTS: Patients with full-thickness DFUs greater than 6 weeks' duration. INTERVENTIONS: Standard wound care plus human fibroblast-derived dermal substitute versus standard wound care alone. MAIN RESULTS: The incidence of amputation/bone resection in the study was 8.9% (28/314) overall, 5.5% (9/163) for patients receiving human fibroblast-derived dermal substitute, and 12.6% (19/151) for patients receiving conventional care (P = .031). Of the 28 cases of amputation/bone resection, 27 were preceded by ulcer-related infection. CONCLUSION: There were significantly fewer amputations/bone resections in patients who received human fibroblast-derived dermal substitute versus conventional care, likely related to the lower incidence of infection adverse events observed in the human fibroblast-derived dermal substitute treatment group.